Revealing Myths and the Truth in Translation - Cresensiana Widi Astuti (Universitas Tarakanita, 2020)
Have you ever been asked to do a translation simply because you speak both Indonesian and English? Or even other languages? There is a myth in our society that when you are bilingual, it means that you have the ability to do translation. This paper is to confirm a statement made by Samuelsson-Brown (2010) that ‘being bilingual means competence in translation’ is only a myth and that the truth is ‘being bilingual does not necessarily include the ability to interpret or translate as translation requires additional skills in order to transfer concepts between languages’. Translation has its specific difficulties any translator needs to overcome. This mini research involved four translators who answered an open-ended questionnaire in a quest to answer a research question, “How do bilingual translators deal with difficulties in translation?” The results showed that the four participants confirmed Samuelsson-Brown’s (2010) statement. And they found some ways to overcome difficulties in translation.